A critical appraisal of guidelines for electronic communication between patients and clinicians: the need to modernize current recommendations. (25th August 2017) - Lee, Joy L; Matthias, Marianne S; Menachemi, Nir; Frankel, Richard M; Weiner, Michael
Abstract: Background: Patient-provider electronic communication has proliferated in recent years, yet there is a dearth of published research either leading to, or including, recommendations that improve clinical care and prevent unintended negative consequences. We critically appraise published guidelines and suggest an agenda for future work in this area. Objective: To understand how existing guidelines align with current practice, evidence, and technology. Methods: We performed a narrative review of provider-targeted guidelines for electronic communication between patients and providers, searching Ovid MEDLINE, Embase, and PubMed databases using relevant terms. We limited the search to articles published in English, and manually searched the citations of relevant articles. For each article, we identified and evaluated the suggested practices. Results: Across 11 identified guidelines, the primary focus was on technical and administrative concerns, rather than on relational communication. Some of the security practices recommended by the guidelines are no longer needed because of shifts in technology. It is unclear the extent to which the recommendations that are still relevant are being followed. Moreover, there is no guideline-cited evidence of the effectiveness of the practices that have been proposed. Conclusion: Our analysis revealed major weaknesses in current guidelines for electronic communication between patients and providers: the guidelines appear to be based on minimal evidence and offer little guidance on how best to use electronic tools to communicate effectively. Further work is needed to systematically evaluate and identify effective practices, create a framework to evaluate quality of communication, and assess the relationship between electronic communication and quality of care.